VARIATIONS IN HEMATOLOGICAL PROFILE DURING DIFFERENT TRIMESTERS OF PREGNANCY - BAGHEL, MANISHA; SAINI, MANPREET; KANDWAL, MAMTA; MODALA, SUDHIR (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objectives: The present study was aimed to determine the hematological parameters in pregnant women during different trimesters. Methods: This is the case–control study, conducted to assess and compare the hematological profile among 120 pregnant (each trimester n=40) and 40 non-pregnant women attending the obstetrics and gynecology department, Santosh Medical College and Hospital, National Capital Region Delhi. SPSS software 17.0 was used for data statistical analysis. Unpaired Student’s t-test used to compare various hematological parameters between different trimesters of pregnancy and non-pregnant females. It is considered that p<0.05 is statistically significant. Analysis of variance with a post hoc test was used. Results: It has been observed in this study that significant differences found in parameters such as systolic blood pressure (SBP), pulse pressure (PP), heart rate, white blood cell (WBC), hematocrit (HCT), Hb%, mean corpuscular volume (MCV), mean corpuscular hemoglobin (Hb) (MCH), and MCH concentration (MCHC). Significant differences in mean hematological values in between the trimesters (p<0.05): 1st trimester (WBC, HB, and HCT), 2nd trimester (SBP, diastolic blood pressure [DBP], PP, WBC, HB, HCT, and MCHC), and 3rd trimester (SBP, DBP, PP, WBC, HB, HCT, MCV, MCH, and MCHC) were seen, but no significant difference in age and erythrocytes count. Conclusion: A considerable change in some hematological values between different trimesters evaluated, also decreased Hb, HCT values, and increased leukocyte values observed in the present study. These changes suggesting that it is very important to follow up hematological parameters of pregnant females during all trimesters of pregnancy so that any late complications can be avoided.